Tax Planning for Article 21 Income - Tutty Nuryati; David Pangaribuan; Defiani Nindasari (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
Tax planning is an effort made by taxpayers or groups of taxpayers to regulate taxes, both income taxes and other taxes, so that they are in the lowest possible position as long as it is still possible by the provisions of the applicable tax regulations. The planning results are not the result of tax savings, tax avoidance, and tax smuggling, so the tax authorities can accept these results. By doing tax planning (tax planning), companies can get more significant income because the tax burden paid by the company is smaller than before doing tax planning. This research used descriptive and comparative methods with a qualitative approach to PT Khatulistiwa. It will show which of the three methods of calculating income tax article 21 is more profitable among the three methods, namely the net, gross, and gross up methods. The results show that from the calculation of Article 21 income tax using the net, gross, and gross up method, the most efficient method of income tax expense is the gross-up method because there is a tax allowance of Article 21 income tax given by the company to employees